1882 Wisc. Laws 389 - (:unkn) unknown (My University, 1882)
Ch. 116, § 1: "It shall be unlawful for any person to sell or use, or have in his possession, for the purpose of exposing for sale or use, any toy pistol, toy revolver, or other toy fire-arm"
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES